2010
DOI: 10.1128/jvi.02061-09
|View full text |Cite
|
Sign up to set email alerts
|

Antibody to Varicella-Zoster Virus Immediate-Early Protein 62 Augments Allodynia in Zoster via Brain-Derived Neurotrophic Factor

Abstract: Varicella-zoster virus (VZV) expresses immediate-early protein 62 (IE62), and zoster is associated with neuropathic pain. Brain-derived neurotrophic factor (BDNF) is involved in the neuronal mechanism underlying pain hypersensitivity. Zoster is associated with prodrome and the robust production of booster antibody to VZV. We hypothesized that the intrathecal production of antibody to IE62 cross-reacting with BDNF and the nerve injury by skin lesions may augment allodynia in zoster by enhancing BDNF activity. Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…The extent that other VZV proteins that are expressed in the rat DRG also needs to be addressed. Of interest is the recent suggestion that antibodies to IE62 augment brain-derived neurotrophic factor (BDNF) induced neuronal changes (Hama et al 2010) (see below).…”
Section: The Rodent Model Of Vzv-induced Painmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent that other VZV proteins that are expressed in the rat DRG also needs to be addressed. Of interest is the recent suggestion that antibodies to IE62 augment brain-derived neurotrophic factor (BDNF) induced neuronal changes (Hama et al 2010) (see below).…”
Section: The Rodent Model Of Vzv-induced Painmentioning
confidence: 99%
“…An intriguing and quite different mechanism is that the expression of VZV IE62 protein and the intrathecal immune response to it are involved in pain. In a mouse model, antibodies to IE62 may stimulate pain hypersensitivity by cross-reacting with BDNF (Hama et al 2010). The authors showed that antibodies reacting to IE62 region from 414 to 429 cross-reacted with the BDNF dimer and augment the expression of BDNF-related transcripts in neurons.…”
Section: Perspectives and Questionsmentioning
confidence: 99%
“…Monoclonal antibodies specific to gB and gE were established as previously reported (24). Polyclonal antibodies against IE62 and IE63 were raised in rabbit and guinea pig, respectively, by immunization with glutathione S-transferasefused recombinant proteins (12). To detect them, Alexa Fluor 488-conjugated anti-mouse, rabbit, or guinea pig IgGs (Invitrogen) were used in the IFA.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…The reactivation of VZV caused zoster in every age group, especially in the elderly, at rates of 3 to 8 per 1,000 person-years in a study of 48,388 zoster patients (46). The major complication of zoster is chronic pain (postherpetic neuralgia); the pain is related to peripheral nerve injury and the activation of brain-derived neurotrophic factor by anti-immediate early (IE) 62 antibody (12). However, the mechanism of VZV latency is not clear.…”
mentioning
confidence: 99%
“…The MAG artifact may also contribute to the discrepancy between reports of high frequencies of neurons that express VZV proteins and the low frequency of neurons that contain VZV genomes based on LCMD and quantitative PCR (19,29). In addition to the presence of neuronal pigments and immunological cross-reactivity between IE62 and neuron-specific brain-derived neurotrophic factor (BDNF), this report identifies an important new variable that confounds the accurate detection of VZV proteins in sensory neurons (8,32).…”
Section: Demonstration Of Mag Reactivity In Human Neuronal Golgi Zonesmentioning
confidence: 91%